BUDAYA HUKUM DALAM PINJAMAN ONLINE: MENJAMIN KESEIMBANGAN ANTARA KEPENTINGAN BISNIS DAN PERLINDUNGAN KONSUMEN - Arini, Ken Sofya; Danial, Putri Sofiani; Purba, Anita Sara; Ririn, Stio (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: This study aims to examine the legal culture in the practice of online lending (pinjol) services in Indonesia, particularly in ensuring a balance between business interests of service providers and consumer protection. The research question addressed is: how can challenges in legal culture help create a balance between consumer protection and business interests in online lending practices, especially concerning inhumane collection methods and the misuse of personal data by illegal lenders. This research employs a normative legal method with a conceptual and statutory approach. The data used are derived from primary legal sources such as the Indonesian Civil Code (KUH Perdata), the Consumer Protection Act, and Financial Services Authority Regulation No. 77/POJK.01/2016 on Information Technology-Based Lending Services, as well as secondary sources such as scholarly literature. The findings indicate that the weakness of legal culture among society and business actors is a key factor behind widespread violations by illegal online lenders. Collection practices involving intimidation and the unlawful dissemination of personal data not only breach positive law but also violate consumers' rights and inflict psychological distress. The study concludes that strengthening legal culture plays a critical role in reinforcing the effectiveness of existing legal norms. Therefore, firm law enforcement, the elimination of illegal lending services, and improvement in public legal literacy are essential to build a fair, safe, and sustainable digital financial ecosystem.Keywords: P2P Lending, Pinjol, Digital